1996
DOI: 10.1006/jabr.1996.0173
|View full text |Cite
|
Sign up to set email alerts
|

A Ring Associated with a Near-Ring

Abstract: Ž. Let N be a right near-ring with identity such that N, q is abelian. Because N enjoys the right distributive property, every right multiplication map on N is an Ž . endomorphism of N, q . The set of all right multiplication maps on N generates Ž . a ring ‫,ޒ‬ a subring of the ring End N . The structure of ‫ޒ‬ is investigated when N is a finite simple near-ring and when N is a finite centralizer near-ring. ᮊ 1996Academic Press, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…The number of residues modified was calculated using ε 367 nm = 11,000 M −1 cm −1 for released trinitrophenyl amino group [24]. Arginine residues were modified by incubating 0.05 mg of RVV-7 in 1 ml of 0.2 M Na-borate, pH 9.8, with 40 mM of 1,2-cyclohexanedione for 3 h at 37 • C [25].…”
Section: Amino Acid Modificationsmentioning
confidence: 99%
“…The number of residues modified was calculated using ε 367 nm = 11,000 M −1 cm −1 for released trinitrophenyl amino group [24]. Arginine residues were modified by incubating 0.05 mg of RVV-7 in 1 ml of 0.2 M Na-borate, pH 9.8, with 40 mM of 1,2-cyclohexanedione for 3 h at 37 • C [25].…”
Section: Amino Acid Modificationsmentioning
confidence: 99%
“…Let A(N ) be the associated ring of N , i.e. the subring of End(N ) generated by P (see [6]). Any element of A(N ) is a finite sum of right multiplication maps from P .…”
Section: The Graded Ring Associated To a Graded Near-ringmentioning
confidence: 99%
“…In this section we consider the setting in [13,Section 3]. For the ease of the reader we provide the pertinent results, definitions and notation.…”
Section: The Representation Of the Right Ring Associated With A Finitmentioning
confidence: 99%
“…In [13,Section 4] it was shown that the subring J of V. generated by the set [p[n]: neN with stab(u) c stab(n(u)), VO ^ v e G] is a nilpotent ideal of K, and that H/1 is isomorphic to a direct sum of complete matrix rings, with TZ the right ring associated with N. Consider the set {£,,,..., £"} of orthogonal idempotents in TZ (with sum 1 R ) as in Section 2, and note that if stab(u, m ) g stab(t;, ( ), with 1 < I, m < p, then, as every element of E^iJlZE,^ has the form it follows from (3) that E^JR-E,^ = [0). Furthermore, in this case for all k and k such that 1 < k < t m , 1 < k < t,, since s t a b^J = stab(i>,J g stab(» (| ) = stab(y (u ,).…”
Section: The Representation Of the Right Ring Associated With A Finitmentioning
confidence: 99%
See 1 more Smart Citation